Openness - Tyng-Ruey Chuang; Rebecca C. Fan; Ming-Syuan Ho; Kalpana Tyagi (Internet Policy Review)
The nature and extent of openness depend on the context and/or disciplinary domain. Earlier usage of the term open was in the context of computer systems. For example, in networked systems of computers, ‘openness’ refers to enabling protocols that connect previously closed systems so that they can communicate with each other. Beyond that, openness has been used to imply a spectrum of meanings, notably since the campaign for open source software development populated the term ‘open’ and its suggested notions of ‘openness’ as freedom, entitlement, or norm. As a social form of organising, ‘openness’ suggests a way of sharing resources. In the corporate context, ‘openness’ refers to more active involvement of stakeholders in the process of value creation.